Immunological characterization of the early human fracture hematoma - Hoff, Paula; Schmidmaier, Gerhard (Immunologic research, 2016)
The initial inflammatory phase of fracture healing is of great importance for the clinical outcome. We aimed to develop a detailed time-dependent analysis of the initial fracture hematoma. We analyzed the composition of immune cell subpopulations by flow cytometry and the concentration of cytokines and chemokines by bioplex in 42 samples from human fractures of long bones <72 h post-trauma. The early human fracture hematoma is characterized by maturation of granulocytes and migration of monocytes/macrophages and hematopoietic stem cells. Both T helper cells and cytotoxic T cells proliferate within the fracture hematoma and/or migrate to the fracture site. Humoral immunity characteristics comprise high concentration of pro-inflammatory cytokines such as IL-6, IL-8, IFNγ and TNFα, but also elevated concentration of anti-inflammatory cytokines, e.g., IL-1 receptor antagonist and IL-10. Furthermore, we found that cells of the fracture hematoma represent a source for key chemokines. Even under the bioenergetically restricted conditions that exist in the initial fracture hematoma, immune cells are not only present, but also survive, mature, function and migrate. They secrete a cytokine/chemokine cocktail that contributes to the onset of regeneration. We hypothesize that this specific microenvironment of the initial fracture hematoma is among the crucial factors that determine fracture healing.